Typological changes in the level of dopamine, cortisol and thyroid hormones in males of Arkhangelsk in the dynamics of year photoperiods - V. N. Zyabisheva; E. V. Tipisova; A. E. Elfimova; I. N. Molodovskaya; V. A. Alikina (Сибирский научный медицинский журнал, 2024)
The aim of the study was to consider typological photoperiodic changes in the levels of dopamine, cortisol and thyroid hormones in males of Arkhangelsk.Material and methods. The study sample included 20 young euthyroid males aged 25–44 years, permanently residing in Arkhangelsk. To study the influence of the photoperiodic factor on the functioning of the endocrine system, four months were selected, which are distinguished by the clearest contrast of daylight hours: March (increased daylight hours), June (maximum daylight hours), September (reduced daylight hours) and December (minimum daylight hours). The concentration of dopamine was determined in the blood plasma, and the indicators of the thyroid profile and cortisol level were studied in the serum.Results. Analysis of the data obtained revealed two types of reactions from the dopaminergic system and cortisol content during the period of minimal daylight hours. Along with the seasonal dynamics of dopamine, there is a change in the activity of the pituitary-thyroid system.Conclusions. In males, whose dopamine levels increase from September to December, the concentrations of cortisol and thyroid hormones also increase, that is, several stress systems are simultaneously activated – the adrenal medulla and cortex, the thyroid gland. Thus, there is a more pronounced reaction to the appearance of seasonal stress factors, which may be due to the rather successful adaptation of the respondents to the environment and may indicate that respondents with dopamine levels decreasing or not changing from September to December either have reduced reserve capacity of the body, or hormones are more actively spent on metabolic processes.